Movements on the nest during incubation by cavity-nesting waterfowl - Mallory, Mark L; McNicol, Donald K (Wildfowl, 1997)
We studied rates of movement on nests by wild, incubating Common Goldeneyes and Hooded Mergansers nesting in north-east Ontario in relation to ambient temperature and stage of incubation. Goldeneyes moved least frequently on the nest at all times. For both species, time intervals between movements were longer for overnight incubation sessions, and intervals remained relatively constant through incubation for morning, afternoon and overnight sessions (except for overnight sessions of Goldeneyes which increased). Our results suggest that ambient temperature influences on-nest activities of cavity-nesting ducks differently than ground-nesting species, and that there is a general relationship between body size and movements on the nest for waterfowl.